ANALISIS KEBUTUHAN SUMUR RESAPAN SEBAGAI PENCEGAHAN LIMPASAN AIR HUJAN PADA PERUMAHAN PUSRI SEMBAWA BANYUASIN - Sartika Nisumanti (UNIVERSITAS INDO GLOBAL MANDIRI, 2018)
In accordance with rapid development in Banyuasin Regency has effected the increased use of land that is built into residential areas. Land use is unwittingly can affect and disrupt the hydrological cycle which causes a negative impact on the environment. It consequenlly, it reduces soil absorption and causes excessive surface run off. Therefore there must be anticipatory steps to reduce rainwater runoff. Infiltration wells can be some to figure out the issue. This research aims to plan the infiltration wells design to reduce rainwater runoff and to know the capacity of drainage channel in Pusri Residence Sembawa Banyuasin. The result of data analysis shows that most of runoff occur in drainage channel of receiver except in segment of Block A1-A2 and Block D1 - D2 and at collector channel. The largest receiver discharge (Q2) is 0.2378 on block V1 - V2. The results of the infiltration wells design is a circle with a diameter of 1 meter and a depth of 3.5 meters. The debit plan for the 2nd year return period with rain intensity 505,9905 mm / hr is 0,0296 m3 / s, while the discharge of the infiltration wells of each plot is 0,0032 m3 / dt for type 36/84. The rain water discharge of infiltration wells with a duration of 30 minutes and the number of house plots is 0.0253 m3 / s, while the discharge plan on channel A-B is 0.0296 m3 / s. After the use of infiltration wells the, remaining discharge of rain water entering on receiver channel on block A-B equal to 0,0265 m3 / s.Keywords: Infiltration Wells, Runoff, permeability